Scenario planning for community development in Vietnam: a new tool for integrated health approaches? - Nguyen, V.; Hung Nguyen-Viet; Phuc Pham Duc; Weise, M. (Informa UK Limited, 2014)
Background: Like many countries in Southeast Asia, Vietnam’s rapid population and economic growth has met challenges in infrastructure development, especially sanitation in rural areas. Objective: As an entry point, we developed scenario planning as an action–research tool in a peri-urban community to identify first steps towards improving their complex sanitation problem and to, systemically, address emerging/re-emerging infectious diseases, as these are commonly linked to unsafe water and inadequate sanitation conditions. As an integrated approach, the process of constructing scenarios allowed us to work across sectors and stakeholders to incorporate this knowledge into a common vision. Design: We conducted focus group discussions to identify and rank driving forces, orally constructed scenarios for the most uncertain drivers, discussed scenario implications and options, and examined the overall process for usefulness and sustainability. During a one-month scoping phase and in between focus group meetings, we carried out household visits which helped us understand the context of data and gather feedback from participants outside of the formal data collection process. Recorded results from these activities were used to develop subsequent tools. Results and Conclusions: The research process gave us insights into how to adapt the scenario planning tool to identify alternative options. This involved choosing boundary partners, negotiating priorities, drawing out participant learning through self-assessment of our process (a prerequisite for changing mental models and thus achieving outcomes), and understanding how conveyed messages may reinforce the status quo. These insights showed the importance of examining research results beyond outputs and outcomes, namely through process.